Regulating professions : the emergence of professional self-regulation in four Canadian provinces - Adams, Tracey Lynn, 1966- (University of Toronto Press, 2018)
"Self-regulation has long been at the core of sociological understandings of what it means to be a 'profession.' However, the historical processes resulting in the formation of self-regulating professions have not been well-understood. In Regulating Professions, Tracey L. Adams explores the emergence of self-regulating professions in British Columbia, Ontario, Quebec, and Nova Scotia from Confederation to 1940. Adams in-depth research reveals the intriguing backstory of those occupations deemed worthy to regulate, such as medicine, law, dentistry, and land surveying, and how they were regulated. Adams evaluates sociological explanations for professionalization and professional regulation by analysing their applicability to the Canadian experience of professional regulation, and especially the role played by state actors. By considering the role of both state actors and professional leaders in making professions in Canada, Adams provides a clearer picture of profession creation and illuminates how important they have been in creating Canadian institutions and building Canadian society."--Provided by publisher